Ecological aspects of hermit crabs (Crustacea, Anomura, Paguroidea) off the northern coast of São Paulo State, Brazil - Fransozo, Adilson [UNESP]; Bertini, Giovana [UNESP]; Braga, Adriane A. [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Springer, 2008)
The occurrence of species of hermit crabs and their ecological distribution in soft bottoms off Ubatuba, São Paulo, Brazil were analyzed. To better understand the distribution of the species in relation to environmental factors, the similarity and species-diversity indexes were calculated. Paguroideans were sampled monthly from January through December 2000. The trawls were made with two otter-trawl nets at 13 different sites, at depths of 2-40 m. Water temperature, salinity, sediment texture, and organic matter content were measured. Gastropod shells occupied by hermit crabs were also assessed. A total of 1,238 specimens was collected, belonging to the families Diogenidae and Paguridae, comprising seven genera and thirteen species. The most abundant hermit crab species were Dardanus insignis (761 specimens) and Loxopagurus loxochelis (351 specimens). Phimochirus holthuisi is newly reported from the São Paulo coast. The highest diversity index was found for the shallower sites near rocky shores. The results of the grouping analysis for sites and species indicated three distinct groups for sites, and four groups for species. This suggests that the occurrence of these anomurans is associated with the environmental and biotic factors analyzed.
Keywords: biodiversity; species distribution; environmental factors; Anomura; hermit crabs; Brazil